Phylogenetic congruence and ecological coherence in terrestrial Thaumarchaeota - Oton, Eduard Vico (ISME J, 2016)
Thaumarchaeota form a ubiquitously distributed archaeal phylum, comprising both the ammonia-oxidising archaea (AOA) and other archaeal groups in which ammonia oxidation has not been demonstrated (including Group 1.1c and Group 1.3). The ecology of AOA in terrestrial environments has been extensively studied using either a functional gene, encoding ammonia monooxygenase subunit A (amoA) or 16S ribosomal RNA (rRNA) genes, which show phylogenetic coherence with respect to soil pH. To test phylogenetic congruence between these two markers and to determine ecological coherence in all Thaumarchaeota, we performed high-throughput sequencing of 16S rRNA and amoA genes in 46 UK soils presenting 29 available contextual soil characteristics. Adaptation to pH and organic matter content reflected strong ecological coherence at various levels of taxonomic resolution for Thaumarchaeota (AOA and non-AOA), whereas nitrogen, total mineralisable nitrogen and zinc concentration were also important factors associated with AOA thaumarchaeotal community distribution. Other significant associations with environmental factors were also detected for amoA and 16S rRNA genes, reflecting different diversity characteristics between these two markers. Nonetheless, there was significant statistical congruence between the markers at fine phylogenetic resolution, supporting the hypothesis of low horizontal gene transfer between Thaumarchaeota. Group 1.1c Thaumarchaeota were also widely distributed, with two clusters predominating, particularly in environments with higher moisture content and organic matter, whereas a similar ecological pattern was observed for Group 1.3 Thaumarchaeota. The ecological and phylogenetic congruence identified is fundamental to understand better the life strategies, evolutionary history and ecosystem function of the Thaumarchaeota.